2024
DOI: 10.1186/s40001-023-01526-4
|View full text |Cite
|
Sign up to set email alerts
|

The impact of SLC10A3 on prognosis and immune microenvironment in colorectal adenocarcinoma

Bangting Wang,
Wentao Fan,
Yuwen Tao
et al.

Abstract: Background SLC10A3, a gene upregulated in pan-cancer, lacks full understanding regarding its prognostic implications and association with immune infiltration in colorectal cancer (CRC). This study comprehensively analyzed SLC10A3 in CRC, evaluating its prognostic significance and influence on the tumor's immune microenvironment. Methods Transcriptomic data from TCGA were obtained to compare SLC10A3 expression in both colorectal cancer (CRC) and nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Moreover, they suggested that SLC10A3 is a possible therapeutic target for LGG [ 41 ]. Furthermore, Wang et al’s study that analyzed public databases indicates that a high DXS253E expression predicts poor prognosis in CRC patients, and they propose that it could be used as an immunotherapy target in CRC given its significant influence on the immune microenvironment [ 23 ]. Similarly, we found that CRC patients with higher DXS253E tumor expression exhibit worse outcomes in respect to both OS and DSS, suggesting that DXS253E can serve as a predictor of CRC prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, they suggested that SLC10A3 is a possible therapeutic target for LGG [ 41 ]. Furthermore, Wang et al’s study that analyzed public databases indicates that a high DXS253E expression predicts poor prognosis in CRC patients, and they propose that it could be used as an immunotherapy target in CRC given its significant influence on the immune microenvironment [ 23 ]. Similarly, we found that CRC patients with higher DXS253E tumor expression exhibit worse outcomes in respect to both OS and DSS, suggesting that DXS253E can serve as a predictor of CRC prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that DXS253E is associated with the infiltration of immune cells in liver cancer [ 22 ]. Similarly, Wang et al analyzed public databases and identified that DXS253E influences the immune microenvironment and is related to poor prognosis in patients with CRC [ 23 ]. However, the exact role of DXS253E in CRC remains to be further determined through the specific experiments.…”
Section: Introductionmentioning
confidence: 99%